IMPROVING STUDENTS’ WRITING SKILL USING GRAMMALY APPLICATION FOR SECOND GRADE IN SENIOR HIGH SCHOOL - Fahmi, Sri; Rachmijati, Cynantia (PROJECT (Professional Journal of English Education), 2021)
Writing is the most important skill in learning a language. Through writing is a way to express student’s ideas, but most students are still deeply mistaken in spelling, grammar, vocabulary and also punctuation. The one way to fix it is to give the students solution with a tool that can help and guide to show their mistake. This research aim of improving students writing skills using Grammarly application. By using Grammarly students are guided to find out students' errors and how to fix it and improve their writing skills using Grammarly application, especially in second grade in senior high school. This research used a qualitative method through pre-test and posttest. The subject of this research is consists of 32 students in second grade in senior high school. The research finding that’s after using Grammarly application can improve student’s ability in writing and express what their thought and felt. It suggested that students should be confident in conveying their ideas into written form as well as maximizing this Grammarly application to help them find errors in writing and can find the correct one. It is recommended that teachers give more serious attention errors of students in writing because of solving. Keywords:  Writing Skill, Grammarly Application